SEROPREVALENCE OF TOXOPLASMA GONDII IN ALPACAS (LAMA PACOS) IN A COMMERCIAL PRODUCTION UNIT OF THE CENTRAL HIGHLANDS OF PERU - Poma De la C., Edwin (2008)
The aim of this study was to determine the seroprevalence of Toxoplasma gondii in alpacas from a commercial unit of SAIS Tupac Amaru, located at Junín Department. A total of 200 blood samples were collected in alpacas of both sexes for the detection of antibodies against T. gondii by the Indirect Hemaglutination Test (IHA). The results indicated that 21 ± 5.6% (42/200) of the samples had antibodies and the titres varied from 1/16 till 1/1024. The Logistic Regression Test failed to obtain statistical relationship between the presence of T. gondii antibodies and the sex of the animal, but there was a significant relationship with age. Young alpacas (8 to 12 months of age) were 2.9 times more susceptible than the groups of >12-36 and >36 months of age. These results could be due to the presence of maternal antibodies, animal management, environmental factors, and the presence of the definitive host. The prevalence found in the present study was considered as moderate.